Kinetic study of quality indices and shelf life modelling of frozen spinach under dynamic conditions of the cold chain. (March 2015) - Dermesonluoglu, E.; Katsaros, G.; Tsevdou, M.; Giannakourou, M.; Taoukis, P.
Highlights: Quality parameters of frozen spinach were studied. Vitamin C, total chlorophyll, texture, sensory of frozen spinach were modelled and validated under dynamic conditions. Developed models can be used for the prediction of frozen spinach quality and shelf life. Abstract: A systematic kinetic study of quality loss of frozen spinach was conducted. Vitamin C, chlorophyll (a, b and total), colour, texture and sensory attributes were measured in frozen leafy spinach. Kinetic models of the selected quality indices were developed to determine the frozen spinach quality loss and calculate product remaining shelf life. Validated kinetic models of quality loss are applied in the evaluation, control and management of frozen spinach in the cold chain. Storage experiments were conducted at isothermal (−5, −8, −12, −18 °C) and non-isothermal temperature conditions ( Teff  = −6.9 °C) to validate proposed shelf life models. The temperature dependence of quality loss was adequately modelled by Arrhenius type equation and activation energy values of 132, 72, 43 and 61 kJ/mol for vitamin C loss, total chlorophyll retention, texture deterioration and overall sensory scoring were calculated respectively. The shelf life at the reference temperature of −18 °C ranged from 400 to 500 days based on the different quality indices. The effects of temperature deviations were quantitatively evaluated and a realistic assessment of the frozen spinach remaining shelf life in the actual cold chain was conducted.